A mobile code collaboration framework for grid computing - Feng, Yuhong (2008)
Data intensive scientific applications often involve diverse, high volume, and distributed data sets. They can generally be viewed as job workflows in which subjobs (ie., nodes or activities) represent application components and dependencies represent the interactions between the components.